Social Network Characteristics, Social Support, and Cigarette Smoking among Asian/Pacific Islander Young Adults. Issue 3 (June 2016) - Pokhrel, Pallav; Fagan, Pebbles; Cassel, Kevin; Trinidad, Dennis R.; Kaholokula, Joseph Keawe'aimoku; Herzog, Thaddeus A.
Abstract: Cigarette smoking may be one of the factors contributing to the high levels of cancer‐related mortality experienced by certain Asian/Pacific Islander (A/PI) subgroups (e.g., Native Hawaiian). Given the collectivist cultural orientation attributed to A/PI groups, social strategies are recommended for substance abuse or smoking cessation treatment among A/PI. However, research examining how social network characteristics and social support relate to smoking across A/PI subgroups has been lacking. This study investigated the associations between social network characteristics (e.g., size, composition), perceived social support, and recent cigarette use across Native Hawaiian, Filipino, and East Asian (e.g., Japanese, Chinese) young adults (18–35 year old). Cross‐sectional, self‐report data were collected from N  = 435 participants ( M age = 25.6, SD = 8.3; 61% women). Ethnic differences were found in a number of pathways linking social network characteristics, perceived social support, and cigarette smoking. Larger network size was strongly associated with higher perceived social support and lower recent cigarette smoking among Native Hawaiians but not Filipinos or East Asians. Higher perceived social support was associated with lower recent smoking among East Asians and Filipinos but not Native Hawaiians. Implications are discussed with regard to smoking prevention and cessation among A/PI.